2015
DOI: 10.1080/14681811.2015.1019665
|View full text |Cite
|
Sign up to set email alerts
|

‘They're just not mature right now’: teachers' complicated perceptions of gender and anti-queer bullying

Abstract: Sexuality education teachers in the USA are often the only officially sanctioned voice in schools charged with teaching students about sexuality and gender. This paper considers the ways in which sexuality education teachers conceptualise gender and anti-queer bullying in order to explore the ways in which teachers understand their own role in the systems of power that lead to gender policing and anti-queer bullying. The study finds that teachers' notions of gender are often linked to essentialist and stereoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 32 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…There is a good reason to predict that neurogenetic essentialism is affected by the content of the genetics curriculum. Studies have found that science textbooks, science teachers, and science students conflate sex and gender (Bazzul & Sykes, ; Bianchini, ; Condit et al, ; Preston, ; Snyder & Broadway, ) and experiments have linked belief in neurogenetic essentialism to genetics texts. For example, in a lab experiment with undergraduate women, Coleman and Hong () randomized individuals to read a science text arguing for either a biological explanation of gender difference or one arguing for a social explanation for gender difference.…”
Section: (De)constructing Gender Concepts Through School Geneticsmentioning
confidence: 99%
“…There is a good reason to predict that neurogenetic essentialism is affected by the content of the genetics curriculum. Studies have found that science textbooks, science teachers, and science students conflate sex and gender (Bazzul & Sykes, ; Bianchini, ; Condit et al, ; Preston, ; Snyder & Broadway, ) and experiments have linked belief in neurogenetic essentialism to genetics texts. For example, in a lab experiment with undergraduate women, Coleman and Hong () randomized individuals to read a science text arguing for either a biological explanation of gender difference or one arguing for a social explanation for gender difference.…”
Section: (De)constructing Gender Concepts Through School Geneticsmentioning
confidence: 99%
“…Teacher Anneloes was worried about false information received through peers or the internet. In line with sex education logics, she constructed the sex education class as a 'space of truth' (Preston, 2016), a truth provided by the teacher that counters the assumed neglect of the topic by parents and the wrong kind of information found online and obtained through peers. The Long Live Love curriculum was used as a guideline, but Anneloes highlighted topics she deemed important for her group, such as virginity and homosexuality.…”
Section: Cuddling In Classmentioning
confidence: 99%
“…Examples of teachers actively contributing to gender harassment include making comments or joking about gay males (Chambers et al ; Meyer, ). Examples of school staff drawing on discourses of victim blame include school counsellors advising trans students to change their gender expression to avoid bullying (Sausa, ), and teachers justifying bullying due to a student's personal presentation (Preston, ). This reframing of the individual as the problem highlights the deeply ingrained nature of gender practices.…”
Section: Disciplinary Practicesmentioning
confidence: 99%
“…Teachers are often unwilling or unable to intervene in instances of gender harassment. Within schools, assumptions about the “normality”of gender bullying, and sometimes the “abnormality” of the victim, means that gender harassment continues to be considered normal (Meyer, ; Preston, ; Sausa, ). Teachers play different roles in gender harassment such as actively contributing or explaining it through a discourse of victim blame, or being silent bystanders (Chambers et al ; Chambers et al ; Meyer, ; Robinson, ; Sausa, ).…”
Section: Disciplinary Practicesmentioning
confidence: 99%